2018
DOI: 10.36469/9812
|View full text |Cite
|
Sign up to set email alerts
|

Using Real World Evidence to Describe Pulmonary Arterial Hypertension Treatment Patterns, Healthcare Resource Utilization, and Costs Associated with PDE-5 Inhibitor Monotherapy

Abstract: Background: Pulmonary arterial hypertension (PAH) is described by proliferation of small pulmonary arteries leading to increased pulmonary vascular resistance, right ventricular failure, and death. Research confirms long-term improvement in composite morbidity and mortality endpoints on some endothelin receptor antagonists alone and in combination with phosphodiesterase type 5 inhibitors (PDE-5is) but not with PDE-5i monotherapy. While current treatment guidelines incorporate these findings, a substantial numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Patients were considered to be adherent to therapy if their PDC was !80%, the commonly accepted threshold for good adherence to PAH therapies 16,17 and other pulmonary and cardiovascular medications. 13,22 Hospitalizations and rehospitalizations within 30 days of discharge were quantified as rates (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients were considered to be adherent to therapy if their PDC was !80%, the commonly accepted threshold for good adherence to PAH therapies 16,17 and other pulmonary and cardiovascular medications. 13,22 Hospitalizations and rehospitalizations within 30 days of discharge were quantified as rates (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Overlapping days from an early refill were counted only once from the end of the previous days’ supply. Patients were considered to be adherent to therapy if their PDC was ≥80%, the commonly accepted threshold for good adherence to PAH therapies 16 , 17 and other pulmonary and cardiovascular medications 13 , 22 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 Delayed diagnosis and initiation of therapy leads to a poor prognosis, 6 which could lead to a significant economic burden for PAH patients. Published studies have estimated healthcare resource utilization (HCRU) and associated costs among patients with PAH 7 , 8 , 9 ; however, there are few studies estimating the excess burden of PAH relative to patients without PH. For example, a recent study reported the direct healthcare costs (2018 USD) were $9915 PPPM for 1293 commercially insured patients with prevalent PAH as compared to $359 for demographically (age, sex, region) matched non‐PAH patients.…”
Section: Introductionmentioning
confidence: 99%